IDENTIFICATION AND DETERMINATION OF SAPONIN CONTENT FROM EXTRACT OF Embelia borneensis BARK - Titin Murtiningsih; Risa Supriningrum; Henny Nurhasnawati (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
Abstract Embelia borneensis known sekilang used by the Dayak Kenyah tribe of Long Temuyat Village, Malinau, North Kalimantan as a fish poison and leech repellent. Sekilang bark extract contains alkaloids, tannins, saponins and flavonoids compounds. The purpose of this study was to determine the type and content of saponins in the methanol extract based on different maceration, reflux, and Soxhlet extraction methods. Saponin content was determined by the gravimetric method. The results showed that the type of saponin contained in sekilang bark extract was triterpenoid saponin. The average saponin content with maceration method was 24.87%, reflux method was 28.97 and soxhlation method was 29.99%. The results of data analysis with one-way anova statistical test showed that there was a significant difference between extraction methods on saponin content of sekilang stem bark with sig value of 0.009 with a significant level of 0.05 (5%).